Mitochondrial DNA: A New Predictor of Diabetic Kidney Disease - Yajing Huang; Jingwei Chi; Fanxiang Wei; Yue Zhou; Yihai Cao; Yangang Wang (International Journal of Endocrinology)
Diabetic kidney disease (DKD) is a common cause of end-stage renal disease, and diagnosis and treatment in time can help delay its progress. At present, there are more and more studies on the pathogenesis of DKD; mitochondrial dysfunction plays an important role in DKD. The occurrence and development of DKD is closely related to epigenetic changes and the interaction between mtDNA, ROS, inflammatory factors, and endothelial damage, which continuously aggravates kidney. The change of mtDNA is both the cause of DKD and the result of DKD. It is of great significance to incorporate the change of mtDNA into the monitoring of patients with diabetes. Existing evidence indicates that changes in mtDNA copy number in blood and urine reflect mitochondrial dysfunction and the severity of DKD. However, large-scale, long-term follow-up clinical trials are still needed to determine the threshold range. By the time, mitochondrial-targeted antioxidants will become a new method for the treatment of DKD and other diabetic complications; mtDNA also can be a therapeutic target for them.